A one‐dimensional silver(I) coordination polymer based on 5‐methyl‐1, 3, 4‐thiadiazol‐2‐amine and pyridine‐2, 3‐dicarboxylate. Issue 6 (1st June 2017) - Fu, Wei-Wei; Li, Juan; Liu, Shu-Ting; Zhao, Dan; Zhou, Xue; Tong, Yang
Abstract : In a novel Ag I coordination polymer based on a dinuclear Ag I cluster consisting of three bridging 5‐methyl‐1, 3, 4‐thiadiazol‐2‐amine ligands and one bridging pyridine‐2, 3‐dicarboxylate ligand, one Ag I atom is located in a four‐coordinated AgN4 tetrahedral geometry and the other Ag I atom is in a tetrahedral AgN3 O geometry. Interchain N—H…O hydrogen bonds extend the one‐dimensional chains into an undulating two‐dimensional sheet. The sheets are further packed into a three‐dimensional supramolecular framework by interchain N—H…O hydrogen bonds. Abstract : The bifunctional pyridine‐2, 3‐dicarboxylic acid (H2 pdc) ligand has one N atom and four O atoms, which could bind more than one Ag I centre with diverse binding modes. A novel infinite one‐dimensional Ag I coordination polymer, namely catena ‐poly[[silver(I)‐(μ2 ‐pyridine‐2, 3‐dicarboxylato‐κ 2 N : O 3 )‐silver(I)‐tris(μ2 ‐5‐methyl‐1, 3, 4‐thiodiazol‐2‐amine‐κ 2 N : N ′)] monohydrate ethanol monosolvate], [Ag2 (C7 H3 NO4 )(C3 H5 N3 S)3 ]·H2 O·C2 H5 OH n, has been synthesized using H2 pdc and 5‐methyl‐1, 3, 4‐thiadiazol‐2‐amine (tda), and characterized by single‐crystal X‐ray diffraction. One Ag I atom is located in a four‐coordinated AgN4 tetrahedral geometry and the other Ag I atom is in a tetrahedral AgN3 O geometry. A dinuclear Ag I cluster formed by three tda ligands with a paddelwheel configuration is bridged by the dianionic pdc 2− ligand into a one‐dimensional coordination polymer. Interchain N—H…O hydrogen bonds extend the one‐dimensional chains into an undulating two‐dimensional sheet. The sheets are further packed into a three‐dimensional supramolecular framework by interchain N—H…O hydrogen bonds.